Analysis of Perceived Trust on Online Buying Behavior Mediated by Online Shopping Attitude in E-Commerce Applications (Study on Universitas Palangka Raya Students) - Welafubun, Evita Veronica; Sintani, Lelo; Sambung, Roby (PT FORMOSA CENDEKIA GLOBAL, 2024)
A study conducted among students of Universitas Palangka Raya aimed to examine the impact of perceived trust on online purchasing behavior, with online shopping attitude as a mediator. The research utilized a descriptive quantitative approach and collected data through questionnaires. The findings revealed that perceived trust significantly influences online shopping attitude. Moreover, the study found that online shopping attitude acts as a mediator between perceived trust and online purchasing behavior. This suggests that consumer trust not only affects their attitude towards online shopping but also plays a role in their purchase decisions. The research highlights the importance for e-commerce businesses to prioritize building consumer trust and creating positive shopping experiences. However, limitations of the study include a limited sample size and the exclusion of external factors that may impact online shopping behavior. Future research should consider a larger sample and explore additional variables that may influence the trust-online shopping behavior relationship.